Microhabitat Characteristics That Regulate Ant Richness Patterns: The Importance of Leaf Litter for Epigaeic Ants - Antonio Cesar Medeiros de Queiroz; Carla Rodrigues Ribas; Filipe Machado França (Sociobiology)
We assessed the effect of conditions and resources on the species richness of epigaeic ants in a cloud forest of the Ibitipoca State Park, Brazil. We hypothesized that the characteristics that are best related with the epigaeic microhabitat affects ant richness more closely than other characteristics. At each sampling site (36 in total) we set up an epigaeic pitfall to capture ants and measured the following environmental variables (conditions and resources): tree density, tree height, circumference at breast height, density of the herbaceous and shrubby vegetation, weight and heterogeneity of the leaf litter, and canopy cover. We built general linear models and used a function that classifies alternative models according to the second-order Akaike information criterion (AICc), in order to assess which environmental variables affect ant species richness. We collected 37 ant species and the models that better explained the variations in ant richness were: (1) null model; (2) heterogeneity of the leaf litter; and (3) weight of the leaf litter. These two environmental variables are positively related to ant richness. It is possible that epigaeic ants are influenced by the high quantity and quality of food and nesting sites provided by a heterogeneous and abundant leaf litter. Relationships between species richness and environmental characteristics should consider different predictor variables related to the microhabitat, since each microhabitat may have a specific pattern and predictor variable. Thus, the understanding of the effects of the microhabitat variables on species richness could help predicting the consequences of anthropogenic impacts